XUV induced hydrogen migration in 5-halouracil. (August 2015) - Castrovilli, M C; Trabattoni, A; Bolognesi, P; O'Keeffe, P; Avaldi, L; Nisoli, M; Calegari, F; Cireasa, R
Synopsis: This work presents a study of the XUV-induced ultrafast molecular dynamics of 5XU conducted with unprecedented temporal resolution. A clear dynamics occurring in 35 fs for both 5FU and 5BrU has been identified and assigned to the hydrogen migration from the C6 site to the C5 site of the molecule. Since 5XU are routinely used as radio sensitizers, the present work provides new important insights in the XUV induced structural changes responsible for the DNA breaking when these molecules are embedded in the DNA chain for radiotherapy.